Peran Dan Strategi Kepala Sekolah Dalam Pengembangan Enterpreneurship - Indah Listia Rahayu; Jumiah Nurhasanah; Tamrin Fathoni (Tamilis Synex: Multidimensional Collaboration, 2023)
Education is an agent of change. Education must be able to bring about major changes in the order of people's lives. The changes expected from education are changes that lead to an increase in the competence of education actors, both among students and educators, especially school principals. The role of the principal is very influential on the success of various programs to achieve school goals. Among the objectives of school institutions is the instillation of an entrepreneurial spirit or called entrepreneurship. The principal's strategy in developing entrepreneurship is carried out to improve the quality of education. The purpose of this study is to determine the role of the principal and his strategy in the development of entrepreneurship in schools. The method used in writing this paper is a literature review carried out by collecting data from various sources needed as a basis for thinking and finding ideas to explore new ideas and thoughts from existing theories. The results of the discussion obtained were the four roles of the principal as an entrepreneur, namely as an entrepreneur who is able to overcome obstacles, as a leader in maintaining flexibility, thinking strategically, pioneering good work and Evaluation of entrepreneurial programs. Meanwhile, the principal's strategy as an entrepreneur is to integrate entrepreneurial values into subjects, establish school business units, and joint use of entrepreneurial results.